March 2022 Placement Ads (The Accounting Review, 2022)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.IMPERIAL COLLEGE BUSINESS SCHOOL, Department of Finance is seeking qualified applicants for faculty positions in its Finance Department at the rank of Associate and Full Professor. Associate and Full Professor applicants should have a proven track record of institution building and service in addition to exceptional scholarship in Accounting. The positions require a strong record of research and demonstrated excellence in teaching and service. Candidates for a Full Professor position should be a world leader in their area of research. Your application will need to include a cv and three research papers. Candidates will need to submit their application via: https://www.imperial.ac.uk/jobs/description/BUS00416/associatefull-professor-accounting Shortlisted candidates will need to arrange for three reference letters to be emailed to: financerecruitment@imperial.ac.uk. Imperial College is committed to equality of opportunity, to eliminating discrimination, and to creating an inclusive working environment. We welcome applicants who will increase diversity within the Department of Finance.TRANSBAY JOINT POWERS AUTHORITY. Come help us transform the future of transportation in the Bay Area. We are looking for an Accounting Director to join our team! The Accounting Director plans, directs, coordinates, and manages the accounting activities of the Transbay Joint Powers Authority (TJPA), which encompass financial reporting, general accounting, capital accounting, accounts receivable, accounts payable, and payroll functions. The Accounting Director supervises technical professional accounting work, requiring knowledge of municipal finance functions, internal controls, government fund accounting, enterprise fund accounting and automated accounting systems. See full job position here: https://tjpa.org/uploads/2021/11/TJPA_Accounting_Director_Brochure_11-9-21.pdf/. Apply today! The salary range is 140,000–160,000 and is dependent upon qualifications and experience. In addition to competitive salaries, TJPA offers flexible benefit plans the successful candidate will be required to pass a background and credit check.REDEEMER HEALTH is seeking a candidate for Senior Director, Hospital Finance. Redeemer Health, a major health system headquartered in suburban Philadelphia with a major hospital, home health and hospice services, and life care facilities, is seeking a visionary leader to head our Hospital Finance team. Reporting to the Redeemer Health Vice President of Financial Reporting and Acute Care, this multi-faceted role oversees the daily reporting of financial and statistical information for the Hospital as compared to budget. Candidates need a college degree in Accounting, Finance, or Business Administration; M.B.A./CPA/CMA/FHFM preferred; 7–10 years of experience in a healthcare facility with knowledge of Generally Accepted Accounting Principles, Medicare, Medicaid regulations, and other reimbursement methodologies along with experience in general ledger and cost accounting methodologies, and budgeting systems; knowledge of forecasting/planning process, Managed Care contracts, and Hospital Cost Accounting and Budgeting Systems, Report Distribution Systems, General Ledger, and Materials Management systems. For more information and to apply, please visit: https://careers.holyredeemer.com/job/27546/Sr-Director-Hospital-Finance . EOE.UNIVERSITY OF CONNECTICUT is pleased to invite applications for a tenure-track faculty position in the Department of Accounting at the rank of Assistant or Associate Professor. For details and to apply, visit https://academicjobsonline.org/ajo/jobs/20386. UConn is an AA/EEO employer.TARLETON STATE UNIVERSITY, Accounting Department is searching for an Assistant Professor of Accounting, primarily responsible for the teaching/learning process and will also participate in the necessary operations of the institution, to start in the Fall 2022 semester. Minimum Requirements: Earned doctorate degree in Accounting, approved by the University and recognized by the Southern Association of Colleges and Schools Commission on Colleges, with appropriate academic credentials verified by Tarleton's faculty credentialing processes. Applications only accepted at https://www.Tarleton.edu/jobs. Tarleton State University is an Equal Opportunity/Affirmative Action/Veterans/Disability Employer. As a member of The Texas A&M System, Tarleton will provide equal opportunity for employment to all persons regardless of race, color, sex, religion, national origin, age, disability, genetic information, veteran status, sexual orientation or gender identity, and will strive to achieve full and equal employment opportunity through The Texas A&M System.PORTLAND STATE UNIVERSITY, School of Business is seeking a research-active, tenure track, tax faculty to join our AACSB accredited Accounting program beginning the Fall of 2022. The accounting faculty are a friendly and collegial group of highly respected researchers (primarily behavioral) with a passion for serving the unique undergraduate and graduate students of Portland State. Come explore our beautiful urban campus and beyond. View the official posting: Link to posting and apply here: https://jobs.hrc.pdx.edu/postings/36372 Email Professor Cass Hausserman at actgsearch@pdx.edu with any questions! School of Business Website: https://www.pdx.edu/business/THE UNIVERSITY OF GEORGIA, Terry College of Business, J. M. Tull School of Accounting seeks applications for a tenure-track Assistant Professor with teaching and research interests in financial accounting. Position will begin Fall 2022 with an anticipated start date of August 1, 2022. Candidates must have a Ph.D. in accounting (completed by August 1, 2022) or a related field with a concentration in accounting. Applications received by January 17, 2022 will receive full consideration. Review of applications will continue until the position has been filled. All application documents must be submitted electronically at: https://www.ugajobsearch.com/postings/232613. Applications submitted in other ways will not be considered. Review of applications will begin immediately and will continue until the position is filled. Questions about the position can be directed to the search committee chair, Frank Heflin, fheflin@uga.edu.CALIFORNIA STATE UNIVERSITY, NORTHRIDGE (CSUN), Department of Accounting is accepting applications for a tenure-track position at the Assistant Professor level beginning Fall 2022. Qualifications: Applicants must demonstrate a commitment to a diverse student population as well as an ability to teach, mentor, and work with diverse students. Successful candidate must have the following credentials: Education: Doctoral degree from an AACSB-accredited institution in accounting or a related business discipline or a J.D. plus L.L.M. (Tax) from an ABA-accredited institution; Publications: Successful candidate must meet and maintain the criterion for Scholarly Academic under the AACSB accreditation requirement and have a demonstrated recent engagement activities involving substantive scholarly activities in their field of accounting. Applicants must submit a letter of application, curriculum vitae, and three current letters of recommendation to the CSUN application website: https://www.csun.edu/careers/. For further detail information, please refer to: https://www.csun.edu/sites/default/files/22-03%20Accounting%20Posting.pdf.FLORIDA STATE UNIVERSITY, Department of Accounting invites applications for a non-tenure-track Lecturer position beginning August 2022. This is a faculty position. Candidates should have an ability to teach undergraduate and graduate courses in the area of taxation, as well as general accounting courses. An established record of excellent teaching at a reputable university is required. Minimum of a Master's degree, but terminal degree is preferred, from an accredited institution in an area of specialization consistent with Accounting and Taxation. Positions will remain open until filled. A criminal history background check will be performed prior to hiring. Applicants should submit their curriculum vitae and three reference letters by email to: acctg-recruiting1@business.fsu.edu. Questions about the position should be directed to Allen Blay, Chair, Department of Accounting, ablay@business.fsu.edu. FSU is an Equal Opportunity/Access/Affirmative Action/Pro Disabled and Veteran Employer. FSU Equal Opportunity Statement can be viewed at: http://www.hr.fsu.edu/PDF/Publications/diversity/EEO_Statement.pdfHUNTINGTON MEDICAL RESEARCH INSTITUTES (HMRI) seeks to hire a Controller to join its Finance and Accounting department. HMRI is an independent, nonprofit organization dedicated to improving lives through patient-focused scientific research. Our scientists' research focuses on the connection between the brain and heart, developing diagnostic tools to help treat common diseases of these vital organs that affect every family. The Controller directs and has immediate responsibility for accounting policies and procedures, the maintenance of financial records, the budget process, and the preparation of financial reports. Grants administration experience and knowledge of laws and regulations pertaining to grants and contracts administration is required, in particular with government grant funding through the National Institute of Health (NIH). Please send application materials (cover letter, resume/cv) and a list of three professional references to: hr@hmri.org for consideration. Visit us at https://hmri.org/ to learn about our research areas.MIDDLE TENNESSEE STATE UNIVERSITY, Jones College of Business invites applicants for the Joey A. Jacobs Chair of Excellence in Accounting. This is a non-tenurable professional practice track position with open rank considered. A Fall 2022 start date is anticipated although an earlier date is possible. The position requires, at minimum, a bachelor's degree in accounting, business, economics, or a closely related field and five years of professional experience with substantial responsibility. The chairholder will engage in teaching and research in accounting; organize seminars and workshops; and collaborate with colleagues across campus and across the country. The position is permanently funded with a multi-million-dollar endowment. Located in Greater Nashville, MTSU offers an outstanding academic atmosphere and an exceptional lifestyle. Apply at: https://careers.mtsu.edu/en-us/listing/. MTSU is an Equal Opportunity, Affirmative Action Employer that values diversity in all its forms. Women, minorities, individuals with disabilities, and protected veterans are encouraged to apply.MIDWESTERN STATE UNIVERSITY, Dillard College of Business Administration (AACSB-accredited) is seeking applicants for Accounting Department Chair, beginning Fall 2022. Located in Wichita Falls, TX, about 125 miles northwest of Dallas, MSU Texas is a 6000-student, COPLAC-member regional university. The Department's 11 full-time faculty members teach courses at undergraduate and graduate levels. Duties include overseeing and developing faculty, curriculum development and scheduling, and resolving student issues. This is a 9-month, tenure-track position normally filled by an Associate or Full Professor. The successful candidate will teach a 2-2 load of face-to-face and online courses with possible summer teaching. A terminal degree in Accounting or related discipline, preferably awarded by an AACSB-accredited university, a track record of excellent in teaching, and demonstrated research and other intellectual contributions required. To apply, please email a letter of application, cv, unofficial undergraduate and graduate transcripts, and three professional references to: lin.wang@msutexas.edu. Salary is competitive.THE UNIVERSITY OF OKLAHOMA, Michael F. Price College of Business, John T. Steed School of Accounting invites applications for an open rank tenured or tenure-track position starting in the 2022–2023 academic year. Applicants will be considered for appointment at the Assistant, Associate, or Full Professor rank based on achievements and experience. Endowed professorships/chairs are available for qualified candidates at the Associate or Full rank. The school's primary teaching needs are in graduate auditing. Qualified individuals may apply at http://apply.interfolio.com/100762. Application materials should include a current vita, working paper to be presented to faculty and doctoral students, evidence of effective teaching, and names and contact information for three references. Questions regarding the search may be submitted to Karen Hennes, khennes@ou.edu. Screening of applications will begin February 4, 2022, but applications will continue to be accepted until the position is filled.